2016
DOI: 10.1016/j.catena.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability and patterns of runoff and runon with different cover crops in an olive orchard (SW Andalusia, Spain)

Abstract: Conventional tillage (CT) and cover crops (CC) trigger different runoff (Q) and runon (Q in) magnitudes and patterns in woody crops. The spatial and temporal stability of these patterns is not well known yet. In this study, we run the uncalibrated DR2-2013 © SAGA v1.1 model (0.5 x 0.5 m of cell size) to simulate time to ponding (Tp), runoff duration (T Q), initial runoff per raster cell (q 0), Q sim and Qin in six olive plots (480 m 2 per plot) during two years (108 rainfall events and 648 simulations). Two pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
(43 reference statements)
2
19
0
Order By: Relevance
“…The observed differences in the effectiveness of water conservation between the cover crop (CC) of common sainfoin and the plant cover of spontaneous vegetation (SP) may be explained by the differences in plant density, much higher in the CC than in the SP. In olive orchards in southern Spain, López-Vicente et al [28] also found different runoff coefficients in runoff crops with homogeneous and heterogeneous plant covers. The wet and stable soil moisture conditions observed in the corridors may be explained by: (i) the occasional tractor traffic that compacts the topsoil, reducing evaporation; (ii) the lack of grapevines in this compartment that clearly reduces the water consumption; (iii) the presence of SP that favored water infiltration; and (iv) the higher content of silt and the lower content of sand in the soils of this compartment in comparison with the rows and inter-row areas (see Table 1).…”
Section: Soil Moisture Dynamicsmentioning
confidence: 96%
See 2 more Smart Citations
“…The observed differences in the effectiveness of water conservation between the cover crop (CC) of common sainfoin and the plant cover of spontaneous vegetation (SP) may be explained by the differences in plant density, much higher in the CC than in the SP. In olive orchards in southern Spain, López-Vicente et al [28] also found different runoff coefficients in runoff crops with homogeneous and heterogeneous plant covers. The wet and stable soil moisture conditions observed in the corridors may be explained by: (i) the occasional tractor traffic that compacts the topsoil, reducing evaporation; (ii) the lack of grapevines in this compartment that clearly reduces the water consumption; (iii) the presence of SP that favored water infiltration; and (iv) the higher content of silt and the lower content of sand in the soils of this compartment in comparison with the rows and inter-row areas (see Table 1).…”
Section: Soil Moisture Dynamicsmentioning
confidence: 96%
“…The value of SDRDiT serves as one of the measures of the temporal stability [28,33,51,52] by comparing its magnitude to the spatial variability of MRDiT. The sensitivity analysis was done for the vineyards' compartments (rows, inter-row areas and corridors) of each field and for the whole study area.…”
Section: Statistical Analysis and Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rüttimann et al () reached a similar conclusion by analyzing runoff data collected in the Swiss Plateau and the Jura. In contrast, López‐Vicente et al () analyzed runoff data from 80 events over six experimental plots with a constant size of 480 m 2 in southwestern Spain and reported that runoff processes over croplands showed highest temporal stability. The existence of temporal persistence of spatial pattern in runoff responses at small spatial scales remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Permanent features in agricultural lands, such as the trunks of woody crops and grooves and rows following straight lines, mainly control overland flow paths, especially in areas with low and moderate slope (López-Vicente et al, 2016). Woody crops, such as vineyards, almond, olive, orange, coffee, tea, and other fruit groves, as well as forest plantations, are cultivated on a significant percentage of the world's agricultural soil.…”
Section: Introductionmentioning
confidence: 99%